Pertumbuhan Penjualan, Pertumbuhan Perusahaan dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Sub Sektor Wadah dan Kemasan Yang Terdaftar di BEI Periode 2019-2021) - Vina Zulia Sari; Taufik Akbar; Aprilia Dian Evasari (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
This research aims to determine the effect of sales growth, company growth and company size on the value of companies in the container and packaging sub-sector listed on the IDX in 2019-2021. The purposive sampling technique used resulted in a sample of 7 companies with observations of 84 companies' quarterly financial reports. The type of data used is secondary data obtained through the official IDX website. The analysis tool used is panel data regression with the help of the eviews application. The research results show that partially sales growth, company growth and company size do not have a significant effect on company value. Simultaneously, sales growth, company growth and company size have a significant effect on company value.